Influence of powder particle size distribution on press-and-sinter titanium and Ti-6Al-4V preforms - Bosman, Hendrik Ludolph (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.